ASSOCIATION OF LEPTIN WITH TYPE 2 DIABETES IN NON-OBESE SUBJECTS - Kazmi, Ahsan; Tariq, Khalid Mehmood; Hashim, Rizwan (Journal of Ayub Medical College Abbottabad, 2012)
Background: South Asians have a high tendency to develop type 2 diabetes even at low BMI. We evaluated serum leptin levels in a group of non-obese type 2 diabetics. Methods: An observational study conducted on 90 subjects, 55 with Type 2 diabetes mellitus, and 35 normal controls (non-diabetics). BMI, waist circumference, serum leptin, and serum glucose were measured. The correlation between these variables was studied by multiple regression analysis. Results: Serum leptin levels were positively correlated with BMI in obese (r=0.976) and non-obese diabetics (r=0.956). Serum leptin was related with diabetes (r= -0.153, p=0.001). Serum leptin was highly correlated with waist circumference in obese than non-obese diabetics, (r=0.753). Mean serum leptin level was 21.4 Î·g/ml in non-obese diabetics and 34.9 Î·g/ml in diabetic group. It is even lower than the non-obese, non-diabetics (23.3 Î·g/ml). Multivariate linear regression analysis between leptin and age, weight, BMI, waist circumference in patients shows only a strong association with BMI in diabetics (p=0.0001), while in non-diabetic it was not significant (p=0.07). Serum leptin was high in diabetics taking oral hypoglycaemic (37.8±19.1 Î·g/ml), while it was low in diabetics taking insulin injections (29.3±24.2 Î·g/ml). Conclusion: Low leptin levels are associated with type 2 diabetes mellitus independent of changes in BMI. Keywords: Leptin, BMI, waist circumference, type-2 diabetes mellitus, serum glucose.